Astrocytes Undergo Metabolic Reprogramming in the Multiple Sclerosis Animal Model - Sofia Pereira das Neves; João Carlos Sousa; Ricardo Magalhães; Fuying Gao; Giovanni Coppola; Sebatien Mériaux; Fawzi Boumezbeur; Nuno Sousa; João José Cerqueira; Fernanda Marques (Cells, 2023)
Multiple sclerosis (MS) is a chronic inflammatory disease of the central nervous system that presents a largely unknown etiopathology. The presence of reactive astrocytes in MS lesions has been described for a long time; however, the role that these cells play in the pathophysiology of MS is still not fully understood. Recently, we used an MS animal model to perform high-throughput sequencing of astrocytes’ transcriptome during disease progression. Our data show that astrocytes isolated from the cerebellum (a brain region typically affected in MS) showed a strong alteration in the genes that encode for proteins related to several metabolic pathways. Specifically, we found a significant increase in glycogen degradation, glycolytic, and TCA cycle enzymes. Together with these alterations, we detected an upregulation of genes that characterize “astrocyte reactivity”. Additionally, at each disease time point we also reconstructed the morphology of cerebellum astrocytes in non-induced controls and in EAE animals, near lesion regions and in the normal-appearing white mater (NAWM). We found that near lesions, astrocytes presented increased length and complexity compared to control astrocytes, while no significant alterations were observed in the NAWM. How these metabolic alterations are linked with disease progression is yet to be uncovered. Herein, we bring to the literature the hypothesis of performing metabolic reprogramming as a novel therapeutic approach in MS.